China's Island Frontier Studies in the Historical Geography of Taiwan - Knapp, Ronald G. (University of Hawai'i Press, 1980)
Until the seventeenth century, Professor Knapp reminds us, Taiwan lay obscure off the southeast coast of China-an island cloaked in anonymity and inhabited principally by aborigines. Then, rather abruptly, the island was thrust into the maelstrom of European commercial expansion in East Asia, which in its wake drew Chinese peasant pioneers across the straits to Taiwan. This is the story, told from many viewpoints, of how Taiwan was transformed over a period of three centuries from a raw frontier to a stable entity with social and economic patterns similar to those found along the coastal mainland of southeastern China.